Towards a Human Cell Atlas: Taking Notes from the Past. Issue 7 (July 2021) - Lindeboom, Rik G.H.; Regev, Aviv; Teichmann, Sarah A.
Abstract : Comprehensively characterizing the cellular composition and organization of tissues has been a long-term scientific challenge that has limited our ability to study fundamental and clinical aspects of human physiology. The Human Cell Atlas (HCA) is a global collaborative effort to create a reference map of all human cells as a basis for both understanding human health and diagnosing, monitoring, and treating disease. Many aspects of the HCA are analogous to the Human Genome Project (HGP), whose completion presents a major milestone in modern biology. To commemorate the HGP's 20-year anniversary of completion, we discuss the launch of the HCA in light of the HGP, and highlight recent progress by the HCA consortium. Highlights: The Human Cell Atlas (HCA) consortium was founded as a collaborative and open effort to create a reference map of the cells in the human body. Organizing a large-scale project such as the HCA draws inspiration from the Human Genome Project (HGP) that was completed 20 years ago. Significant progress has been made by the HCA community, including profiling more than 39 million cells from 15 major organs to date. The expected impact of the HCA is illustrated by its use during the coronavirus disease 2019 (COVID-19) pandemic.